The Association Between Loneliness and Inflammation: Findings From an Older Adult Sample - Van Bogart, Karina; Engeland, Christopher G.; Sliwinski, Martin J.; Harrington, Karra D.; Knight, Erik L.; Zhaoyang, Ruixue; Scott, Stacey B.; Graham-Engeland, Jennifer E. (Frontiers in Behavioral Neuroscience, 2022)
Loneliness has been linked to poor mental and physical health outcomes. Past research suggests that inflammation is a potential pathway linking loneliness and health, but little is known about how loneliness assessed in daily life links with inflammation, or about linkages between loneliness and inflammation among older adults specifically. As part of a larger investigation, we examined the cross-sectional associations between loneliness and a panel of both basal and LPS-stimulated inflammatory markers. Participants were 222 socioeconomically and racially diverse older adults (aged 70-90 years; 38% Black; 13% Hispanic) systematically recruited from the Bronx, NY. Loneliness was measured in two ways, with a retrospective trait measure (the UCLA Three Item Loneliness Scale) and an aggregated momentary measure assessed via ecological momentary assessment (EMA) across 14 days. Inflammatory markers included both basal levels of C-reactive protein (CRP) and cytokines (IL-1β, IL-4, IL-6, IL-8, IL-10, TNF-α) and LPS-stimulated levels of the same cytokines. Multiple regression analyses controlled for age, body-mass index, race, and depressive symptoms. Moderation by gender and race were also explored. Both higher trait loneliness and aggregated momentary measures of loneliness were associated with higher levels of CRP (β = 0.16, p =.02; β = 0.15, p = .03, respectively). There were no significant associations between loneliness and basal or stimulated cytokines and neither gender nor race were significant moderators. Results extend prior research linking loneliness with systemic inflammation in several ways, including by examining this connection among a sample of older adults and using a measure of aggregated momentary loneliness.